Farm Ponds in Coastal Saline Zone of West Bengal A Techno-economic Feasibility Study - Babu, R Ravi; Mishra, Purnima (Journal of Agricultural Engineering, 2001)
Farm pond excavation in individual farmer’s fields for storing excess rain water during the monsoon and reusing it for life saving irrigation to the crops during the post-monsoon period, besides practising pisciculture, is gaining popularity among the farmers of coastal saline zone. With a view to assess the techno-economic feasibility of farm pond excavation under field conditions in the coastal belt, a field study in 24 Parganas (South) district of West Bengal was conducted during. The study revealed that in the pre-developmental stage only mono-crop of Aman (kharif) Paddy was cultivated whereas in the post-developmental stage (i.e. after excavation of farm pond) the farmers were able to grow different kinds of vegetables and pulses besides practising pisciculture. Further, the techno-economic feasibility has established that the farm ponds have tremendous potential in turning the mono-cropped coastal saline area into multi-cropped/crop-diversified area and improve the cropping intensity and thereby the farmers’ income.